The Ambiguity of Work: Work Practice Stories of Meaningful and Demanding Consultancy Work - Humle, Didde Maria (Nordic Journal of Working Life Studies, 2014)
This article contributes to the current debate among organizational and work-life researchers on the double-sided nature of knowledge work, which offers great freedom and satisfaction on the one hand and the potential to be overly demanding and stressful on the other. This contribution involves drawing on the results of an ethnographic case study of a consultancy house; more specifically, it comprises an exploration of the narrative identity work of consultants as they perform work practice stories of self, work, and the organization negotiating why the work they do is both challenging and rewarding. The type of knowledge work explored is characterized by its immaterial nature in the sense that the primary input is the competences, knowledge, and commitment of the consultants and the output is the joy, success, and satisfaction of candidates, clients, and collaborators. The article contributes by showing that some of the elements perceived to make the work meaningful and rewarding are the same ones also described as potentially demanding and challenging. Furthermore, the article contributes by arguing that studying work practice stories as (ante)narrative identity work provides a rich source of empirical material in the examination of how we create meaning in relationship to the work we do and the organizations by which we are employed.